Investigating the influence of urban land use on asbestos concentration and identifying the most vulnerable areas in Shiraz, Iran - Samira Norzaee; Siamak Darvishali; Mahdi Farzadkia; Ahmad Jonidi Jafari; Mitra Gholami; Abbas Shahsavani; Majid Kermani (Scientific Reports)
Abstract This study investigated asbestos fiber concentrations and associated health risks in Shiraz over a period of one year and examined their relationship with various land use factors. Samples were analyzed using phase-contrast microscopy (PCM), and health effects were assessed using the EPA’s IRIS method. We examined the relationship between asbestos fiber concentrations and road network density, population, number of bus stations, and green space. The results showed that 10% of the sampling sites in Shiraz had low asbestos fiber concentrations, 20% had medium concentrations, 60% had high concentrations, and 10% had very high concentrations. The mean ELCR for asbestos inhalation was 1.44 × 10−4, indicating a cancer risk for 1.44 out of every 10,000 people. The highest ELCR values were found in the west, near the Shiraz Ring expressway, and in the southeast, near high-traffic areas. Additionally, no positive correlation was found between asbestos concentrations and population, bus stations, or green space, but there was a significant positive correlation with road network density. Motor vehicle traffic is the primary source of asbestos pollution, posing a significant health risk. Traffic control measures and replacing asbestos in brake pads with alternative materials are necessary to reduce pollution in Shiraz.